Biobased iron pellet production : Assessment of the availability and sustainability of biomass as fuel for iron ore pellet production in LKAB - Kemi, Magnus (Mittuniversitetet, Institutionen för naturvetenskap, design och hållbar utveckling (2023-), 2023)
Iron production accounts for substantial shares of global coal use and GHG emissions. LKAB is Europe’s largest iron company and Sweden’s fourth-largest emitter of GHGs. To reduce its emissions, LKAB might implement biomass in iron ore pelletisation. It is therefore important with information on how the biomass demand can be met and what the environmental implications may be, but available research focuses on contexts which are irrelevant for LKAB. This study aims to fill this knowledge gap by investigating the extent to which LKAB can replace coal with biomass in iron ore pelletisation by assessing the availability of biomass as well as its environmental and economic performance relative to coal. The study includes slash, industrial residues, pellets, and willow. The biomass potential is assessed using statistics and calculations. The environmental performance is assessed based on an LCA combined with a qualitative sustainability assessment, covering land-use change (LUC), biodiversity, toxins, chemicals, eutrophication (toxic-chem-eut), and compliance with EU sustainability criteria. The economic performance is based on price statistics. In general, all assessed biomass sources can meet LKAB’s potential demand, but requires sourcing from different locations, at different prices, with different environmental impacts, and with different market effects. In northern Sweden (“Norrland”) slash is largely unused and has a very good potential to supply LKAB with biomass. Industrial residues have a good potential on the domestic level but lower potential regionally. The potential of domestically produced pellets is limited but the demand can be met by increased production or imports. Willow currently has a low potential, but there is good potential to increase domestic production. In general, the biomass fuels have substantially lower environmental impact than coal. The LCA indicates that slash and industrial residues have the lowest environmental impact, pellets has slightly higher, and willow has higher impact in most ...